INTERNAL REFORMS AT ICE DURING THE LAST 10 YEARS - Fumero Paniagua, Gerardo (2006)
The 80’s, witnessed deep changes in the information and telecommunicationstechnologies. The globalization catalyzed the economic integration process and a newvision of open markets, in witch telecommunications services lost their category ofpublic utility and became a service subject to private forces.In Costa Rica, important internal reforms were carried out in ICE. In the industry, thereforms that the country could adopt in the near future would decide if we keep ourpublic utility solidarity model, witch has been a key element of integral development ofthe country, or if we choose a model in witch would deeply affect poor people.